Advanced landing gear fibre Bragg grating sensing and monitoring system - Grooteman, F.P.; Goutagny, R.; Davies, C.; Leest, T. van; Platt, I.; Symons, J. (My University, 2022)
In this paper an advanced optical-based landing gear load sensing and monitoring system is presented. The system measures strains using fibre Bragg grating sensor that are converted into loads and torque at the landing gear wheels and provides this data for use by the aircraft systems for integration with aircraft health monitoring, hard landing detection, flight management, flight controls and ground controls. A complete sensing system was developed in the European Union Clean Sky 2 Joint Technology Initiative Advanced Landing Gear Sensing and Monitoring (ALGeSMo), described herein. This involved: the integration of optical fibres into a composite structure, the development of an optical harness (cabling and connectors) meeting aircraft installation requirements, the readout of the optical fibre sensors with state-of-the-art miniature optoelectronics and the processing and communication of the data. Apart from specific tests on the various components, a bespoke test rig was developed to rigorously test the whole sensing and monitoring system on an A320 main landing gear slider tube to validate the performance of the system. The system-level tests performed on the test rig showed a very good correlation with applied actuator loads and additional conventional strain and temperature sensors. It demonstrates that loads along all three axis of the landing gear and the torque about the wheel axle can be accurately measured. Tests performed at cold and elevated temperatures, however, revealed that the generally applied one-dimensional temperature compensation equation is not accurate enough for this application, due to the non-uniform non-stationary temperature field. The ALGeSMo research activities have advanced the state of the art in several key areas for the deployment of optical sensing systems for safety-critical applications, such as integration of optical fibres into composite material, robust optical connections, avionic-compliant optical interrogator and landing gear load measurement up to technology readiness level technology readiness level 5.